1997
DOI: 10.1038/sj.ijir.3900269
|View full text |Cite
|
Sign up to set email alerts
|

On life satisfaction in male erectile dysfunction

Abstract: A consecutive series of 413 impotent men and 109 References rated their satisfaction with life as a whole and with seven different domains of life along a six graded scale ranging from very satis®ed to very dissatis®ed. In a subsample of impotent men treated with PGE 1 these self-ratings were repeated applying the concept that dissatisfaction re¯ects an aspirations/achievement gap and successful treatment leads not only to increased sexual well-being but also to increased satisfaction with life as a whole. Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
145
1
11

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(165 citation statements)
references
References 5 publications
8
145
1
11
Order By: Relevance
“…For example, it has been shown in previous studies that men with ED report deficits in several broader areas of their life, including their general emotional satisfaction, general happiness, productivity, intimacy and safety. 17,20 The psychological and QOL findings of the present study support the recent proposal by FuglMeyer et al 18 that presence of ED has its impact on men's QOL because of the creation of a sexual aspiration-achievement gap. According to FuglMeyer et al, 18 when sex is regarded as an important aspect of a man's life, but he is unable to fulfil his sexual goals (for example, through presence of ED), the gap between sexual aspirations and achievement widens, resulting in an overall decline in QOL.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…For example, it has been shown in previous studies that men with ED report deficits in several broader areas of their life, including their general emotional satisfaction, general happiness, productivity, intimacy and safety. 17,20 The psychological and QOL findings of the present study support the recent proposal by FuglMeyer et al 18 that presence of ED has its impact on men's QOL because of the creation of a sexual aspiration-achievement gap. According to FuglMeyer et al, 18 when sex is regarded as an important aspect of a man's life, but he is unable to fulfil his sexual goals (for example, through presence of ED), the gap between sexual aspirations and achievement widens, resulting in an overall decline in QOL.…”
Section: Discussionsupporting
confidence: 80%
“…7,8,18,19 It has been well demonstrated that general and healthrelated QOL of men with ED are frequently impaired, 19 and that the presence of this sexual dysfunction is associated with many different areas of a man's QOL. For example, it has been shown in previous studies that men with ED report deficits in several broader areas of their life, including their general emotional satisfaction, general happiness, productivity, intimacy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Answers were scored from 1 (almost never/never) to 5 (almost always/always), with 0 indicating no sexual activity. (4) Life Satisfaction Checklist [15], week 0 and week 12; this is an 8-item questionnaire assessing the patients' quality of life (life as a whole, sexual life, partnership relation, family life, contacts with friends, leisure situation, vocational situation, financial situation). Answers are scored from 1 (very dissatisfying) to 6 (very satisfying).…”
Section: Methodsmentioning
confidence: 99%
“…Scores were graded on a scale of 1-5, with one for never or almost never, and five for always or almost always, with no intercourse noted as zero. In addition, the IIEF-erectile function (IIEF-EF) domain was also evaluated (the sum of Questions 1-5 plus Question 15), which ranges from severe ( £ 10), to moderate (11)(12)(13)(14)(15)(16), to mild-moderate (17)(18)(19)(20)(21), to mild (22)(23)(24)(25), to normal ( > 25). The 12-week LOCF score was used.…”
Section: Efficacy Parametersmentioning
confidence: 99%
“…. 18 Fugl-Meyer QOL scores were graded on a scale of 1-6, with one for very unsatisfying, and six for very satisfying.…”
Section: Efficacy Parametersmentioning
confidence: 99%